2011
DOI: 10.1038/nm.2306
|View full text |Cite
|
Sign up to set email alerts
|

Alum interaction with dendritic cell membrane lipids is essential for its adjuvanticity

Abstract: As an approved vaccine adjuvant for use in humans, alum has vast health implications, but, as it is a crystal, questions remain regarding its mechanism. Furthermore, little is known about the target cells, receptors, and signaling pathways engaged by alum. Here we report that, independent of inflammasome and membrane proteins, alum binds dendritic cell (DC) plasma membrane lipids with substantial force. Subsequent lipid sorting activates an abortive phagocytic response that leads to antigen uptake. Such activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
299
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 356 publications
(316 citation statements)
references
References 44 publications
9
299
1
3
Order By: Relevance
“…If future studies determine that the adjuvant properties of chitosan are inflammasome-dependent, then formulations consisting of particles small enough to be phagocytosed would likely lead to maximum effectiveness. Interestingly, the commonly used adjuvant alum also stimulates the NLRP3 inflammasome (27,53,54), although recent studies have suggested that the ability of alum to activate the inflammasome is not required for its adjuvanticity (55). Chitosan has also been utilized to encapsulate DNA (56), and the primary amines of chitosan can be exploited to conjugate antigens, thus allowing direct delivery into cells.…”
Section: Discussionmentioning
confidence: 99%
“…If future studies determine that the adjuvant properties of chitosan are inflammasome-dependent, then formulations consisting of particles small enough to be phagocytosed would likely lead to maximum effectiveness. Interestingly, the commonly used adjuvant alum also stimulates the NLRP3 inflammasome (27,53,54), although recent studies have suggested that the ability of alum to activate the inflammasome is not required for its adjuvanticity (55). Chitosan has also been utilized to encapsulate DNA (56), and the primary amines of chitosan can be exploited to conjugate antigens, thus allowing direct delivery into cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this model we envision direct interaction of macrophages with the biomaterial surface. Interestingly, microparticles like alum can also induce syk activation in DCs, which raises the possibility that these cells have a similar ability to respond to biomaterials (20). However, the DC response to alum was shown to be caspase-1 independent, implicating the involvement of a separate pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Kool et al (2) first demonstrated in mice that injection of alum results in the release of uric acid, an endogenous danger signal, which then activates inflammatory dendritic cells (DCs) to prime CD4 + T cells. Shortly after, Flach et al (3) showed that alum crystals directly interact with membrane lipids on DCs, initiating a signaling cascade that increases cell surface levels of LFA-1 and ICAM-1, which, in turn, enables CD4 + T cells to bind with higher affinity to the DCs. Some studies suggested that the release of dsDNA from damaged and dying host cells, which is induced by alum injection, may contribute to priming of Th2 CD4 + T cells (4,5) and enhance MHC class II-mediated Ag presentation, prolonging CD4 + T cell interactions with DCs (5).…”
mentioning
confidence: 99%